Family Socialization Influences on Developing Emotion Regulation skills among children - medjahdi, tahar; aiche, sabah (Journal of Social Sciences and Humanities, 2020)
Emotional organization is not something that is born with us. Young children do not have emotional organizational skills, so it is the family who has a responsibility to help their children learn the skills of emotional organization. Developmental psychologists have always considered the expression emotional parentage an integral part of a child's emotional and social competence. Parental emotional expression in the context of the family is of particular importance as it is the primary context in which children first learn the rules of emotional presentation and acquire others' understanding of emotional expression. Family is one of the important life contexts that affect in the healthy development of children. The stimuli offered by the family - especially within the parent-child relationship - play a crucial role in child development. Emotional regulation develops in the context of the family, where social interactions and multifaceted family relationships affect emotional behavior and children's abilities to manage their feelings. In this article, we will discuss the role of the family in developing the skills of Emotional regulation through: Emotional expression, supportive and warm responses to parents, emotional regulation of children, family emotional climate, direct interventions for emotional management, interpersonal conflicts, parent-child dialogue. Although we focused in our article only on family influences, this does not negate the presence of other factors that contribute to emotional organization, whether within the family such as brotherly relations or the quality of the parenting relationship or outside the family in the larger social context that includes friends, school and others